PEMANFAATAN LAGU MENGGUNAKAN KOSA-KATA BAHASA ARAB UNTUK MENINGKATKAN HAFALAN SISWA MI MIFTAHUL ULUM BANYUPUTIH KIDUL-JATIROTO-LUMAJANG - Hidayatul Munawaroh; Nabila Nailil Amalia; Utari Dwi Mayasari (Institut Kariman Wirayudha Sumenep Madura, 2025)
This study aims to examine the effectiveness of using songs in teaching Arabic vocabulary (mufrodat) at MI Miftahul Ulum Banyuputih Kidul. The background of the study is based on students' low ability to memorize vocabulary in Arabic language learning. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation involving both students and teachers. The findings indicate that the use of songs containing Arabic vocabulary significantly enhances students' memorization skills. Songs help create an enjoyable learning atmosphere, boost student motivation and active participation, and strengthen memory retention of the taught vocabulary. Although challenges such as pronunciation difficulties and understanding word meanings still exist, this method is considered highly effective and recommended for Arabic language instruction, especially at the elementary (Madrasah Ibtidaiyah) level.